Lower bioelectrical impedance phase angle is associated with COPD and is a marker for increased risks in elderly COPD patients - Qian, JinHua; Xu, Min; Zhang, ZhaoXi; Wu, YuJie; Wang, GuoQing; Fan, XiaoYun (Frontiers in Medicine, 2026)
IntroductionThe phase angle (PhA), derived from bioelectrical impedance analysis (BIA), serves as an indicator of cellular health and body composition. While associated with muscle strength and exercise capacity in various conditions, its clinical relevance in chronic obstructive pulmonary disease (COPD) requires further characterization. This study aimed to evaluate the relationship between PhA, muscle strength, and physical function among individuals with COPD.MethodsBetween June 2024 and August 2025, 112 male patients with COPD and 20 healthy male controls were enrolled in this cross-sectional study. Assessments included pulmonary function, body composition via BIA, handgrip strength, knee extension strength, walking speed, and other clinical indicators. Relationships were analyzed using multivariable linear and least absolute shrinkage and selection operator (LASSO) regression models.ResultsPhA values were significantly lower in COPD patients than in healthy controls. Stratification of COPD patients by PhA revealed that a lower PhA was associated with progressively worse muscle strength, exercise capacity, and other clinical markers. Multivariable linear regression analyses demonstrated that a lower PhA was independently associated with slower walking speed (β = 0.061, p < 0.001) and reduced knee extension strength (β = 1.15, p = 0.002). Furthermore, PhA was selected as a key predictor in a prognostic model for severe physical impairment derived from the LASSO regression analysis.ConclusionIn this cross-sectional study, a lower PhA is independently associated with muscle weakness and impaired physical performance in men with COPD. These findings suggest that PhA may serve as a useful biomarker for assessing nutritional and functional status in this population. However, the cross-sectional design precludes causal inference, and the diagnostic utility of PhA for COPD itself is not established.